The Roman Gask system tower at Shielhill South, Perthshire: excavations in 1973 and 1996 - Woolliscroft, David J; Hoffmann, Birgitta (Proceedings of the Society of Antiquaries of Scotland, 1999)
Reports on previously unpublished excavations of 1973 and subsequent investigations in 1996 which revealed a double ditched four post multi-period timber tower forming part of a group of four such towers at the southern end of the Flavian frontier.